Advances in the role of STAT3 in macrophage polarization - Xia, Tingting; Zhang, Meng; Lei, Wei; Yang, Ruilin; Fu, Shengping; Fan, Zhenhai; Yang, Ying; Zhang, Tao (Frontiers in Immunology, 2023)
The physiological processes of cell growth, proliferation, differentiation, and apoptosis are closely related to STAT3, and it has been demonstrated that aberrant STAT3 expression has an impact on the onset and progression of a number of inflammatory immunological disorders, fibrotic diseases, and malignancies. In order to produce the necessary biological effects, macrophages (M0) can be polarized into pro-inflammatory (M1) and anti-inflammatory (M2) types in response to various microenvironmental stimuli. STAT3 signaling is involved in macrophage polarization, and the research of the effect of STAT3 on macrophage polarization has gained attention in recent years. In order to provide references for the treatment and investigation of disorders related to macrophage polarization, this study compiles the pertinent signaling pathways associated with STAT3 and macrophage polarization from many fundamental studies.